STUDY OF FACTOR INFLUENCING COMMUNITY TO SUPPORT THE WASTE MANAGEMENT IN THE KAHAYAN RIVER BASIN OF PALANGKA RAYA CITY - Tarita Aprilani Sitinjak; Whendy Trissan; Petrisly Perkasa; Ni Putu Diah Agustin Permanasuri; Mega Kurniawati; Nathanael; Ruslan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Littering behaviour directly into the river is still carried out by the majority of people in the Mendawai and Flamboyant Bawah areas along the Kahayan river in Palangka Raya city. Since shaping positive behavior about waste management is crutial, research on aspects or variables that influence people's intention to support household waste management activities was conducted. This quantitative research aim to determine the variables that influence the community in supporting household waste management. A questionnaire was designed and distributed in order to gain primary data. To collect the secondary data, study literature about household management was conducted. Descriptive statistic was proposed to understanding the demographic respondent’s characteristics. Structural Equation Model-Partial Least Square (SEM-PLS) was proposed to analyze the relationship between the research variable’s. By applying Descriptive Statistic, it was found that the respondent dominated by women as a housewife and age more than 35 years old. Furthermore, through Structural Equation Model-Partial Least Square (SEM-PLS) method it was found that institutional and regulatory (X4) and information aspects (X5) are variables that positively and significantly affect community support for waste management in Mendawai and Flamboyan Bawah settlements located on the Kahayan river in Palangka Raya City. Firm institutional and regulation also sustainable information about the household waste management positively increasing the intention of society to support the household waste management.